2022
DOI: 10.3389/fendo.2022.1050709
|View full text |Cite
|
Sign up to set email alerts
|

“Liver–gut” axis: A target of traditional Chinese medicine for the treatment of non-alcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) occurs when fat accumulates in the liver even without excessive alcohol intake. Among the current therapeutic approaches for NAFLD, lifestyle modification with dietary changes and regular exercise is the mainstay treatment. With the rise of intestinal microecology, regulation of the “liver–gut” axis can be an effective treatment for NAFLD. This review aimed to assess the modulation of the liver–gut microbiota axis with traditional Chinese medicine (TCM) as a therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…In recent years, the development and application of herbs and phytochemicals has become a research hotspot. Multiple studies have shown that the hepatoprotective activities of various herbs and phytochemicals were closely related to their regulatory effects on the gut-liver axis [70,71].…”
Section: Herbs and Phytochemicalsmentioning
confidence: 99%
“…In recent years, the development and application of herbs and phytochemicals has become a research hotspot. Multiple studies have shown that the hepatoprotective activities of various herbs and phytochemicals were closely related to their regulatory effects on the gut-liver axis [70,71].…”
Section: Herbs and Phytochemicalsmentioning
confidence: 99%
“…Therefore, the traditional herbal compounds or formulas are usually targeted at harmonizing the function of “liver and spleen”. In preclinical studies, they are indicated to be beneficial in suppressing hepatic inflammation, regulating lipid profile and intestinal flora, and reducing LFC 78,79 . It is worth mentioning that the clinical trials on compound Chinese herbal medicines are all registered on the Chinese Clinical Trial Registry (http://www.chictr.org.cn), with no conclusive results yet (Table 3).…”
Section: Advances In Nafld/nash Treatment Regimens In Chinamentioning
confidence: 99%
“…The emerging field of intestinal microecology has shed light on the potential of regulating the gut-liver axis as a treatment for NAFLD. 4 Numerous recent studies have identified a link between gut microbiome changes and NAFLD’s pathogenesis. Certain bacterial strains, such as Lactobacillus , Bifidobacterium , Akkermansia muciniphila , and Bacteroides uniformis , have been found to have protective effects against NAFLD in animal models.…”
Section: Introductionmentioning
confidence: 99%